The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s00167-022-07063-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell-based therapies have disease-modifying effects on osteoarthritis in animal models. A systematic review by the ESSKA Orthobiologic Initiative. Part 1: adipose tissue-derived cell-based injectable therapies

Abstract: Purpose The aim of this systematic review was to determine if adipose tissue-derived cell-based injectable therapies can induce disease-modifying effects in joints affected by osteoarthritis (OA). Methods A systematic review was performed on three electronic databases (PubMed, Web of Science, Embase) according to PRISMA guidelines. A synthesis of the results was performed investigating disease-modifying effects in preclinical studies comparing injectable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 105 publications
1
14
0
Order By: Relevance
“…31 Meanwhile, preclinical models have documented evidence of the disease-modifying effects of ADMSCs for the treatment of knee osteoarthritis in macroscopic, histologic, and immunohistochemical evaluations. 42 According to preclinical studies, the promising effects of ADMSCs could skew the biochemical environment of osteoarthritis into regenerative and anti-inflammatory conditions via paracrine effects. 11,23,40,42 A recent midterm clinical study showed significant improvement in cartilage changes between 2 and 3 years after a single IA injection of ADMSCs based on serial MRI evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…31 Meanwhile, preclinical models have documented evidence of the disease-modifying effects of ADMSCs for the treatment of knee osteoarthritis in macroscopic, histologic, and immunohistochemical evaluations. 42 According to preclinical studies, the promising effects of ADMSCs could skew the biochemical environment of osteoarthritis into regenerative and anti-inflammatory conditions via paracrine effects. 11,23,40,42 A recent midterm clinical study showed significant improvement in cartilage changes between 2 and 3 years after a single IA injection of ADMSCs based on serial MRI evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…42 According to preclinical studies, the promising effects of ADMSCs could skew the biochemical environment of osteoarthritis into regenerative and anti-inflammatory conditions via paracrine effects. 11,23,40,42 A recent midterm clinical study showed significant improvement in cartilage changes between 2 and 3 years after a single IA injection of ADMSCs based on serial MRI evaluation. 32 Thus, structural cartilage improvement requires a longer follow-up to reflect the regenerative and chondroprotective effects of ADMSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cavallo et al reported that bone marrow aspirate concentrate (BMAC) obtained from the iliac crest and proximal tibia presents the potential for osteogenic and chondrogenic differentiation as well as mesenchymal marker expression [9]. Perucca Orfei C et al reported in a systematic review that injectable adipose‐derived cell‐based therapies showed positive effects on joint tissues in animal osteoarthritis models, provided a structural/macroscopic improvement in both the cartilage and synovial membrane properties compared to untreated osteoarthritis joints and reduced the serum and synovial fluid levels of cartilage destruction markers [22].…”
Section: Discussionmentioning
confidence: 99%